Pengaruh Tinggi Air dan Padat Tebar yang Bervariasi terhadap Pertumbuhan dan Kelangsungan Hidup Benih Ikan Lele Sangkuriang (Clarias gariepinus) - Nurdini, Nurdini; Lahming, Lahming; Patang, Patang (Nekton, 2023)
The growth of catfish seeds can be influenced by many factors including high water and seed stocking density. The research objective was to analyze the effect of high air and stocking density of different fish on the growth and maintenance of Sangkuriang catfish fry. This type of quantitative research with an experimental approach. The research was an experiment using a completely randomized design (CRD) factorial. Data processing uses SPSS Version 22 with two-way ANOVA analysis if there are differences, it will be followed by Tukey HSD. The research analysis showed that there was an effect of varying stocking density treatments on the survival of fish fry and absolute growth, while the high air treatment only had an effect on the survival of Sangkuriang catfish fry. The research yielded a water height of 13 cm and a stocking density of 15 individuals/liter was the treatment with the highest survival rate for catfish seeds with a value of 74.4%, while for exclusive weight growth, the treatment was 10 cm water height and a stocking density of 15 individuals/liter of 0.94 g.